RENDEMEN FINIR PADA MESIN ROTARY BERDASARKAN KELOMPOK JENIS KAYU PADA INDUSTRI KAYU LAPIS DI PT. SURYA SATRYA TIMUR - Alfian Alfian; Lusyiani Lusyiani; Noor Mirad Sari (Universitas Lambung Mangkurat, 2020)
This research aims to find out processing veneer waste and rendemen of wood type group one and wood type group two on rotary machine in the plywood industry at PT. Surya Satrya Timur Banjarmasin. Data in the form of volume values of raw materials (input) and veneer volume results of peel logs on rotary machines (output) for each group of wood species. The input and output values of the stripping process are taken on weekdays (excluding machine maintenance schedules) in May 2017. The value of veneer rendemen on rotary machine by commercial timber type one is ranged between 59.40-86.85% with average value 71.00%. The value of veneer rendemen on rotary machine by commercial timber group two is ranged from 21.00 to 90.08% with average value 54.17%. The t-test analysis showed that the treatment cause significant differences to veneer rendemen value on the rotary machine at PT. Surya Satrya Timur. Differences in the value of rendemen due to factors that affect is the quality of raw materials. The average value of veneer waste on a rotary machine for commercial timber group one 29.00% that means can be categorized as efficient production. Meanwhile, the average value of veneer waste on a rotary machine for commercial timber group is 45.83%, that means can be categorized less efficient. In general, the average value of veneer rendemen on rotary machine 62.58% and the waste 37.42% which means the use of raw materials can be categorized as efficient.Keyword: veneer; wood type groups; rendemen; waste